2022
DOI: 10.1038/s41392-022-01191-9
|View full text |Cite|
|
Sign up to set email alerts
|

The Hippo signalling pathway and its implications in human health and diseases

Abstract: As an evolutionarily conserved signalling network, the Hippo pathway plays a crucial role in the regulation of numerous biological processes. Thus, substantial efforts have been made to understand the upstream signals that influence the activity of the Hippo pathway, as well as its physiological functions, such as cell proliferation and differentiation, organ growth, embryogenesis, and tissue regeneration/wound healing. However, dysregulation of the Hippo pathway can cause a variety of diseases, including canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
75
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 222 publications
(113 citation statements)
references
References 399 publications
2
75
0
Order By: Relevance
“…In addition, we constructed a hub mRNA model for predicting the nuclear grade. Biological processes always involve interactions among genes expressed by interaction networks which are controlled by driving hub genes [14] , [15] . Exploring the predictive performance of hub genes can help understand the association between radiomic features and genes.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we constructed a hub mRNA model for predicting the nuclear grade. Biological processes always involve interactions among genes expressed by interaction networks which are controlled by driving hub genes [14] , [15] . Exploring the predictive performance of hub genes can help understand the association between radiomic features and genes.…”
Section: Discussionmentioning
confidence: 99%
“…After MST1/2 is activated by the upstream kinase thousand-and-one amino acid kinase (TAOK) ( 5 ) or dimerization itself ( 6 ), it can combine with SAV1 through its C-terminal Sav/RASSF/Hpo (SARAH) domain to phosphorylate SAV1 ( 2 ). Phosphorylated SAV1 can interact with LATS1/2 to assist LATS1/2 phosphorylation ( 7 ).…”
Section: Hippo Pathway and Yes-associated Proteinmentioning
confidence: 99%
“…In addition to TEAD1–4, YAP can interact with Runx1/2, BRD4, Smad, and other transcription factors after entering the nucleus ( 2 , 10 , 20 ).…”
Section: Hippo Pathway and Yes-associated Proteinmentioning
confidence: 99%
See 1 more Smart Citation
“…The latest research found that palmitoylation is an important protein modification mode of TEAD binding with the YAP/TAZ, and its unique binding mode makes the TEAD easy to target [ 160 ]. VT3989 and IK-930, two TEAD palmitoylation inhibitors, have been studied in human clinical trials [ 161 , 162 , 163 , 164 ]. Table 2 shows potential drugs targeting YAP/TAZ and its upstream and downstream pathways in pre-clinical trials and clinical trials.…”
Section: Future Prospects For Clinical Applicationsmentioning
confidence: 99%